Batman unmasked : analyzing a cultural icon - Brooker, Will, 1970- (Bloomsbury Academic, 2000)
Over the sixty years of his existence, Batman has encountered an impressive array of cultural icons and has gradually become one himself. This fascinating book examines what Batman means and has meant to the various audiences, groups and communities who have tried to control and interpret him over the decades. Brooker reveals the struggles over Batman's meaning by shining a light on the cultural issues of the day that impacted on the development of the character. They include: patriotic propaganda of the Second World War; the accusation that Batman was corrupting the youth of America by appear.